Planting date effects on the germinability and seedling vigour of Abutilon theophrasti (Malvaceae) seeds - E. Nurse, Robert; DiTommaso, Antonio; A. Ramirez, Ricardo (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2004)
AbstractAbutilon theophrasti (Malvaceae) is a troublesome annual weed in many maize and soybean cropping systems of Canada and the United States. Seeds of A. theophrasti exhibit physical dormancy. Differences in the growing environment of parent plants may influence the germinability of seeds and vigour of seedlings produced by this species because of variation in resource allocation to seed development. Thus, the germinability of seeds and subsequent seedling vigour were examined for A. theophrasti plants grown in monoculture at a density of 4.2 plants m-2 under varying natural photoperiods in central New York State. Treatments were established by transplanting A. theophrasti seedlings on three dates: 15 May, 4 June, and 30 June 2000, which correspond to peak photoperiods of 15, 14, and 13 hours, respectively. Seeds produced under the shorter photoperiod (13 h) weighed, on average, 1.5 mg less than seeds produced under the longer photoperiod (15 h). Contrary to expectations, seeds of A. theophrasti that matured under shorter photoperiods had lower germinability (80%) than seeds produced under longer photoperiods (98%). Early radicle growth, a measure of seedling vigour, did not differ between the photoperiod treatments. Environmental conditions other than photoperiod (i.e. water availability) prevailing during the 2000-growing season may have influenced seed coat thickness and consequently affected the germinability of seeds.